Implementasi Manajemen Rantai Pasok (Supply Chainn Management) Pada PT. Yakult Indonesia Persada - Ririn Astiyani; Bangun Putra Prasetya (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research discusses the implementation of supply chain management at PT. Yakult Indonesia Persada, Mojokerto, East Java branch. This research uses a literature study analysis method or literature review with secondary data sources. This research explains the main role in supply chain management implemented by PT. Yakult Indonesia Persada starts from suppliers, production processes, retail, distributors, to consumers. PT. Yakult Indonesia Persada collaborates with several local and foreign suppliers to obtain main raw materials such as skim milk powder from Australia and New Zealand, sucrose and dextrose from Cirebon, packaging materials, namely polystyrene plastic ore, from China. The production process is carried out using sophisticated high-tech machines and is carried out by competent human resources (HR) to create standardized products, distribution is carried out by PT. Yakult Indonesia Persada, namely by using land and sea routes with two distribution systems, namely direct sale distribution which is carried out using backup cars to be distributed to traditional shops such as food stalls to modern shops such as supermarkets, and yakult lady, namely distribution carried out by women who has been equipped with knowledge about Yakult products to disseminate information to consumers using motorbikes or bicycles. With this distribution system, it has proven to be quite good, as proven by PT. Yakult Indonesia Persada has regular consumers spread throughout almost all of Indonesia.